High mobility group box 1 protein regulates osteoclastogenesis through direct actions on osteocytes and osteoclasts in vitro. Issue 10 (20th May 2019) - Davis, Hannah M.; Valdez, Sinai; Gomez, Leland; Malicky, Peter; White, Fletcher A.; Subler, Mark A.; Windle, Jolene J.; Bidwell, Joseph P.; Bruzzaniti, Angela; Plotkin, Lilian I.
Abstract: Old age and Cx43 deletion in osteocytes are associated with increased osteocyte apoptosis and osteoclastogenesis. We previously demonstrated that apoptotic osteocytes release elevated concentrations of the proinflammatory cytokine, high mobility group box 1 protein (HMGB1) and apoptotic osteocyte conditioned media (CM) promotes osteoclast differentiation. Further, prevention of osteocyte apoptosis blocks osteoclast differentiation and attenuates the extracellular release of HMGB1 and RANKL. Moreover, sequestration of HMGB1, in turn, reduces RANKL production/release by MLO‐Y4 osteocytic cells silenced for Cx43 (Cx43 def ), highlighting the possibility that HMGB1 promotes apoptotic osteocyte‐induced osteoclastogenesis. However, the role of HMGB1 signaling in osteocytes has not been well studied. Further, the mechanisms underlying its release and the receptor(s) responsible for its actions is not clear. We now report that a neutralizing HMGB1 antibody reduces osteoclast formation in RANKL/M‐CSF treated bone marrow cells. In bone marrow macrophages (BMMs), toll‐like receptor 4 (TLR4) inhibition with LPS‐RS, but not receptor for advanced glycation end products (RAGE) inhibition with Azeliragon attenuated osteoclast differentiation. Further, inhibition of RAGE but not of TLR4 in osteoclast precursors reduced osteoclast number, suggesting that HGMB1 produced by osteoclasts directly affects differentiation by activating TLR4 in BMMs and RAGE in preosteoclasts. Our findings also suggest that increased osteoclastogenesis induced by apoptotic osteocytes CM is not mediated through HMGB1/RAGE activation and that direct HMGB1 actions in osteocytes stimulate pro‐osteoclastogenic signal release from Cx43 def osteocytes. Based on these findings, we propose that HMGB1 exerts dual effects on osteoclasts, directly by inducing differentiation through TLR4 and RAGE activation and indirectly by increasing pro‐osteoclastogenic cytokine secretion from osteocytes. Abstract : Apoptotic osteocytes release elevated levels of the proinflammatory cytokine, high mobility group box 1 protein (HMGB1), and apoptotic osteocyte conditioned media (CM) promotes osteoclast differentiation. We now report that increased osteoclastogenesis induced by apoptotic osteocytes CM is not mediated through HMGB1/RAGE activation and that direct HMGB1 actions in osteocytes stimulate pro‐osteoclastogenic signal release from apoptotic osteocytes. Based on these findings, we conclude that HMGB1 exerts dual effects on osteoclasts, directly promoting differentiation via TLR4 and RAGE activation and indirectly increasing pro‐osteoclastogenic cytokine release from osteocytes.